DEVELOPMENT OF WATER TREATMENT SACHETS FROM THE SEEDS OF MORINGA OLEIFERA AND ACTIVATED CARBON - Zakaria, Hidayatul Aini; Mansor, Wan Salida Wan; Shahrin, Norshazira (MATTER: International Journal of Science and Technology, 2018)
Water is a common chemical substance that is essential to all known forms of life. Purified water is essential for living a healthy life as such everyone should have access to it. Pollution of water bodies is a major health issue in many fast growing cities where population growth far exceeds the rate of development of wastewater collection and treatment infrastructure. Wastewater treatment is an essential process that removes impurities from the water, making the water safe for domestic usage as well as drinking. Conventional wastewater treatment includes the usage of alum which would deteriorate health conditions with prolonged consumption. This research is focused on the development of water treatment sachets from the seeds of moringa oleifera and activated carbon. Characterization of the water treatment sachets was made by utilizing Brunauer, Emmett and Teller (BET), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Turbidity Meter. BET analysis shows and isotherm linear graph which proved that the activated carbon have larger surface area, pore size and volume compared to seeds of Moringa Oleifera, this finding correlates well with existing literatures. This also indicates that the level of adsorption in activated carbon is higher and more capable of removing impurities in water compared to Moringa Oleifera, From XRD results, it is verified that both samples, activated carbon and seeds of Moringa Oleifera are amorphous in structure. FTIR analysis indicate that the functional group in both samples of activated carbon and seeds of Moringa Oleifera are similar with literatures. As the ratio of seeds of Moringa Oleifera increases, the removal become faster since it depends on the initial concentration. Turbidity Meter analysis showed that higher volume of Moringa Oleifera will increase the percentage of impurities removal. This study had proved that the combination of Moringa Oleifera and activated carbon is suitable for high turbidity water treatment and further study should be conducted before these water treatment sachets are available for public use.